Teachers and Students’ Perception of Using Audio and video in English Listening Activities at SMA Adabiah 2 Padang - Shanny Pilochutari; Lafziatul Hilmi (Journal of English Language Teaching, 2023)
This research aimed to examine teachers’ perception of using audio and video for listening, students’ perception about using audio and video, also teachers’ difficulties in teaching listening using audio and video. This study used a descriptive qualitative methodology. For this study, the author applied a questionnaire and interview, with 16 statements for the questionnaire and 8 main questions for the interview. The participants were 72 students and three teachers of SMA Adabiah 2 Padang. According to the research's findings, students believed that the use of video is better than the use of audio. Video helped them more in learning listening, because it has visual cue, pictures, sound, and sometimes subtitles. Student thought that they understand the listening material better in video forms. Related to motivation and interest, students also felt that video makes them more enthusiastic in learning. Along with it, they believed that video improves their listening comprehension. The researcher found that teacher that teachers' perceptions substantially influenced their instructional techniques and the choice of the materials that the pupils will learn. It is thought to be crucial to recognize the opinions of educators because it is essential knowledge to build international language instruction. However, from the findings, it can be concluded that most of the English teachers used audio for teaching listening regularly. It is effective for the learning and easy to prepare or use.